Advanced engineering design an integrated approach - Benavides, Efren Moreno (Woodhead publishing in mechanical engineering, 2012)
This book provides engineers and students with a general framework focusing on the processes of designing new engineering products. The procedures covered by the framework lead the reader to the best trade-offs to ensure maximum satisfaction of the customer's needs, meeting the lowest cost expectations, ensuring the lowest environmental impact and maximising profits and best positioning in the marketplace. Chapters discuss the engineering tools that are compatible with these goals and sustainable activity.